Branding dan Pemasaran Kemplang Panggang Desa Tebing Gerinting Selatan Kecamatan Indralaya Selatan - Ardiansyah; Trecy Austin; Suhendra (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2022)
In the context of implementing the Tridarma of Higher Education, one of them is through community service as a form of community service. This community service takes the theme of the Thematic Community Service Program "Village Branding: goes to Global" Stisipol Candradimuka Palembang with a focus on research and service, namely Entrepreneurship. This Entrepreneurship Program aims to carry out Branding and Marketing of home-based production which is one of the potential villages that can be developed in order to help increase the income of the local community, namely Branding Kemplang Baked Home Products in Tebing Gerinting Selatan Village, South Inderalaya District, Ogan Ilir Regency, South Sumatra Province. The activity begins with the socialization of marketing strategies given to home-based businesses and product packaging that will raise the business potential of the people of Tebing Gerinting Selatan Village. Marketing strategy so that their products which were previously only marketed by self-taught can expand to all regions of South Sumatra and even Globally. In compiling the results of this research and service using a qualitative approach with direct interview techniques to business actors. From the results of the analysis, it was found that several problems in product development, including home-based businesses still use conventional marketing methods and lack of innovation in terms of production, packaging, and marketing. The results of this activity are expected to change the mindset and action patterns of business actors to improve product quality, packaging and marketing strategies for Kamplang Panggang, Tebing Gerinting Selatan Village..